2021
DOI: 10.1021/acs.jmedchem.1c00956
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Photoactivatable Real-Time Monitoring of a Controlled Drug Delivery Platform

Abstract: The current anticancer therapies are limited by their lack of controlled spatiotemporal release at the target site of action. We report a novel drug delivery platform that provides on-demand, real-time, organelle-specific drug release and monitoring upon photoactivation. The system is comprised of a model anticancer drug doxorubicin, an alkyltriphenylphosphonium moiety to target mitochondria in cancer cells, and a hydroxycinnamate photoactivatable linker that is covalently attached to the drug and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…Sasmal et al have recently reported drug delivery platform 216 based upon a key cinnamate photoactivation. 218 In the same way as Mosey and Floreancig (Scheme 7), Sasmal et al have employed Murphy's triphenylphosphonium directing group to target the mitochondria of the relevant cell type, and the success of this approach was evident in the fluorescence microscopy studies following treatment of HeLa cells with 216 (92% of cellular uptake into the mitochondria within 2 h). Use of one (365 nm) or two-photon irradiation (700 nm) 219 of 216 proved successful in releasing the doxorubicin reporter group.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Sasmal et al have recently reported drug delivery platform 216 based upon a key cinnamate photoactivation. 218 In the same way as Mosey and Floreancig (Scheme 7), Sasmal et al have employed Murphy's triphenylphosphonium directing group to target the mitochondria of the relevant cell type, and the success of this approach was evident in the fluorescence microscopy studies following treatment of HeLa cells with 216 (92% of cellular uptake into the mitochondria within 2 h). Use of one (365 nm) or two-photon irradiation (700 nm) 219 of 216 proved successful in releasing the doxorubicin reporter group.…”
Section: Reviewmentioning
confidence: 99%
“…An alternative platform for effective intramolecular cyclisation systems have been realised by the trimethyl-lock linkers, these take advantage of a Thorpe-Ingold effect in tandem with repulsion from an adjacent aromatic methyl group: recently, these have been thoroughly reviewed by Klahn. [220][221][222][223] Jullien and Schmidt have reported valuable kinetic data of their rates of cyclisation, utilising a photoactivatable self-immolative system 217 that, upon trigger activation, results in a 6-exo-trigcyclisation (218), favoured by steric hindrance, resulting in lactonization of the linker to give 219 in ca. 3 minutes liberating the fluorescent reporter 220 (Scheme 49).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cell-or site-selective targeting units could be integrated into the construct. Singh et al developed a mitochondria-targeting system (using an alkyltriphenylphosphonium (TPP) targeting moiety) with an o-hydroxycinnamate PPG, releasing doxorubicin upon light irradiation [58] (Figure 8). Although the o-hydroxycinnamate PPG itself is not In the former case, upon TP excitation the TP-absorbing unit donates an electron to the pyridinium PPG unit (* referring to the photoexcited state), leading to a photochemical reaction and the release of the cargo [8].…”
Section: Selected Applications Of Ppgsmentioning
confidence: 99%
“…Additionally, cell-or site-selective targeting units could be integrated into the construct. Singh et al developed a mitochondria-targeting system (using an alkyltriphenylphosphonium (TPP) targeting moiety) with an o-hydroxycinnamate PPG, releasing doxorubicin upon light irradiation [58] (Figure 8). Although the o-hydroxycinnamate PPG itself is not fluorescent, upon its photoinduced isomerization and cyclization a fluorescent coumarin derivative is formed, that could be exploited for the real-time monitoring of the release process.…”
Section: Selected Applications Of Ppgsmentioning
confidence: 99%